PENGARUH KEBUGARAN JASMANI TERHADAP HASIL BELAJAR DALAM PEMBELAJARAN PENJAS SISWA SEKOLAH DASAR: The Influence of Physical Fitness on Learning Outcomes in Physical Education Learning for Elementary School Students - Prima Duta, Afdal; Dinangsit, Dinar; Sudirjo, Encep (Fakultas Ilmu Keolahragaan Unimed, 2025)
Abstract: This study aimstodeterminetheeffectofphysicalfitnessonlearningoutcomes in PhysicalEducation, Sports, andHealth (PJOK). The methodused in this study isdescriptivequantitative. The researchsampleconsistedof 40 students, physicalfitness data wasobtainedthroughthe Indonesian PhysicalFitnessTest (TKJI), whilelearningoutcomes were obtainedfromodd semester reportcardscores. StatisticalanalysisusedtheShapiro-WilknormalitytestandtheMann-Whitney U testtoseedifferences in learningoutcomes. Studentswithhighphysicalfitness (12 students) had anaveragelearningscoreof 90.3, whilestudentswithlowfitness (28 students) had anaveragescoreof 85.7. The Mann-Whitney testproduced a significancevalueof 0.034 (p <0.05), whichindicates a significantdifferencebetweenthetwogroups. Thus, itcanbeconcludedthatphysicalfitness has a significanteffecton PJOK learningoutcomes. Studentswithbetterphysicalfitnesslevelstendtobemoreactive, do not tirequickly, and are more optimal in participating in learning, whichultimately has animpactonachievinghighergrades. Keywords:Kebugaran Jasmani, Hasil Belajar, PJOK, Siswa Sekolah Dasar, Mann-Whitney